Study on the effect of vibration on solidification structures in the vibration cast‐rolling process. Issue 4 (14th April 2021) - Wang, H.; Qu, C.; Zheng, Y.; Du, F.
Abstract: In the vibration cast‐rolling process, the metal material is in the state of sub‐rapid solidification. Based on the principle of solidification and random theory, the relation between the vibrating process with sub‐rapid solidification and the number of new crystal nuclei was deduced. The theoretical analysis, numerical simulations and experiments of sub‐rapid solidification under vibration were performed. The results show that the modified Cellular Automaton‐Finite Element model can predict the solidified microstructure and size of crystal grains. The results also show that vibration with chilling can effectively promote the production of free crystal nuclei. With a higher frequency of vibration, the area of the equiaxed zone can increase, and the grains can be smaller. Abstract : The study of the effect of vibration on solidification structures of AlSi9Cu3 in the vibratory cast‐rolling process shows that a higher frequency of vibration with chilling can effectively promote the production of free crystal nuclei, the increase of equiaxed zone area, and the refinement of grains.